2018
DOI: 10.12659/msm.907660
|View full text |Cite
|
Sign up to set email alerts
|

L-Theanine Protects H9C2 Cells from Hydrogen Peroxide-Induced Apoptosis by Enhancing Antioxidant Capability

Abstract: BackgroundL-theanine is a non-protein amino acid in green tea, and its hepatoprotection and neuroprotection have been verified. However, whether L-theanine can prevent cardiomyocytes from apoptosis is unclear yet. This study evaluated the protective effects of L-theanine on H2O2-induced heart injury in vitro.Material/MethodsThe certified H9C2 cells were pretreated with L-theanine (0 mM, 4 mM, 8 mM, and 16 mM) for 24 h, followed by 160 μM H2O2 solution for 4 h. The cell viability and antioxidant indices were as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 39 publications
1
16
0
Order By: Relevance
“…Furthermore, EGCG could decrease myocardial oxidative stress and free fatty-acid levels, thus inhibiting the development of heart failure induced by the heart/muscle-specific deletion of manganese superoxide dismutase in mice [74]. Theanine could protect H9c2 cells against hydrogen peroxide-induced apoptosis via enhancing antioxidant capacity, such as elevating the activities of glutathione peroxidase and SOD, and reducing the levels of ROS, nitric oxide, and oxidized glutathione [75].…”
Section: Experimental Studiesmentioning
confidence: 99%
“…Furthermore, EGCG could decrease myocardial oxidative stress and free fatty-acid levels, thus inhibiting the development of heart failure induced by the heart/muscle-specific deletion of manganese superoxide dismutase in mice [74]. Theanine could protect H9c2 cells against hydrogen peroxide-induced apoptosis via enhancing antioxidant capacity, such as elevating the activities of glutathione peroxidase and SOD, and reducing the levels of ROS, nitric oxide, and oxidized glutathione [75].…”
Section: Experimental Studiesmentioning
confidence: 99%
“…Evidences indicate that aging causes the decline in mitochondrial function and antioxidant defense systems in vivo [ 5 , 7 ]. Accumulated reactive oxygen species (ROS) leads to oxidative damage [ 21 ]. These ROS stimulate oxidative burst, and contribute to the damages of cell membrane and DNA [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…These ROS stimulate oxidative burst, and contribute to the damages of cell membrane and DNA [ 22 ]. As a major pathophysiological mechanism for heart diseases, oxidative stress participates in the occurrence and development of cardiac hypertrophy [ 7 , 21 ]. Under normal conditions, ROS are scavenged by cellular antioxidant defense mechanisms [ 2 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Central nervous system damage will cause reactive oxygen species (ROS) overload, and the subsequent oxidative stress reaction will further cause apoptosis and cell death. The mechanism of the antioxidant effect of L-theanine was mainly related to reversing the ROS overload [35,36]. Furthermore, studies have confirmed that L-theanine also plays a positive role in the fight against oxidative stress in various cells, such as hepatocytes, neurons, and cardiomyocytes [34,37].…”
Section: Lysozyme Adsorption Capacity Of the Plga/go-thmentioning
confidence: 93%